Keeping alive enterprises while embracing unprecedented COVID-19 restrictions - Soriano, Vicente; Corral, Octavio Jorge (Therapeutic Advances in Infectious Disease, 2021)
COVID-19 is rapidly expanding globally, with more than 1,800,000 cases and 105,000 deaths to date (April 11, 2020) (www.worldometers.info). The WHO upgrade to pandemic, the emergency declaration in the United States, and the nationwide quarantines implemented in most European countries will last for over the announced 4 weeks. In addition to major health consequences, the coronavirus crisis is expected to harm most economies very deeply.
Keywords: Emerging; Scopus